Musculoskeletal aspects of respiratory function in cystic fibrosis: a cross-sectional comparative study - Niklas Sinderholm Sposato; Kristofer Bjerså; Marita Gilljam; Louise Lannefors; Monika Fagevik Olsén (European Clinical Respiratory Journal)
Background Respiration is an intricate interaction between visceral and musculoskeletal structures. In cystic fibrosis (CF), the airways and lungs are subject to progressive obstruction and destruction. However, knowledge about the musculoskeletal aspects of respiratory function and symptoms is still limited in this patient group.Methods In a cross-sectional comparative study, 21 adults with CF enrolled at the Gothenburg CF Centre were matched with 42 healthy controls. The two groups were examined and compared in terms of thoracic mobility, respiratory muscle strength, lung function, and musculoskeletal pain in accordance with a predefined protocol.Results Significant differences were observed between the groups in the number of tender points, thoracic excursion, forced vital capacity (FVC), and forced expiratory volume (FEV). The CF group also demonstrated a tendency toward reduced function in other measurements, although these were not statistically significant.Conclusion This cross-sectional study revealed that people with CF have reduced thoracic mobility and an increased prevalence of muscular tender points, alongside decreased lung function, compared to healthy controls. These findings stress the need for greater emphasis on the often-overlooked musculoskeletal aspects of CF care, especially as people with CF are living longer and may require more musculoskeletal health support.